La psicología clínica hoy: pluriversos (2009)
ABSTRACT: Clinical psychology is not one, like is not the one general Psychology that is its source, this does that the same nature of clinical psychology is based on a pluridiversidad of thought currents that are the referring epistémico of all clinical psychologist. In addition to being clinical psychology a diversity of theories, is one of the so many diverse fields that they conform Psychology in as much applied science. To be field, it is necessary to consider conditions that must be fulfilled such as: definition of the object, which is determined by the psychological current; a relation particular subject-object that guarantees a method taken by means of strategies, specific techniques and tools to it and the search of an aim of the action. The field also is identified by referring ones as they are: the definition and specific origin of the applied actions, and finally, a field is also defined to share with other disciplines its action, that is to say, to maintain relations interdisciplinary.